Global burden and trends of high alcohol use-related injuries from 1990 to 2030: a comprehensive assessment of self-harm and interpersonal violence, transport injuries, and unintentional injuries using global burden of disease 2021 - Yuan, Qiheng; Chen, Zhixuan; Sun, Bianjin; Zheng, Chenzhi; Kang, Yutong; Lou, Yongliang; Zheng, Meiqin (Frontiers in Public Health, 2025)
BackgroundHigh alcohol use (HAU) is a major global public health concern, contributing to injuries such as Self-harm and interpersonal violence (SIV), Transport injuries (TI), and Unintentional injuries (UII). However, comprehensive global assessments of HAU-related injury burden remain limited.MethodsUsing data from Global Burden of Disease (GBD) 2021, we estimated HAU-related mortality and disability-adjusted life years (DALYs) from 1990 to 2021 across 204 countries and regions. We analyzed trends in Age-Standardized Disability-Adjusted Life Years Rate (ASDR) and Age-Standardized Mortality Rate (ASMR), examined Socio-demographic index (SDI) disparities, and employed age-period-cohort (APC) and Bayesian APC (BAPC) models for future projections. Frontier analysis identified countries with the greatest potential for burden reduction.ResultsDespite the decline in ASDR and ASMR in overall global injuries, Low-middle SDI regions continue to experience increasing SIV and TI burdens (ASDR rose from 57.25 to 70.55; 25.08 to 30.8 respectively), while UII remains high in High-middle and High SDI countries (The ASDR were 57.94 and 59.12 respectively). Young adults and the elderly bear the greatest burden. BAPC projections indicate that China, India, and several high-burden nations will see further increases in DALYs and ASDR by 2030, highlighting the need for urgent interventions.ConclusionTargeted policy measures, such as raising the legal drinking age, strengthening alcohol control for young people in Low and Low-middle-SDI regions, and enhancing older adults healthcare services in High-SDI regions, are essential to mitigate HAU-related injuries. Evidence-based, SDI-adapted strategies can significantly reduce this burden.